Synthesis of nitrogenase and heterocysts by Anabaena sp. CA in the presence of high levels of ammonia. - Bottomley, P J (1979)
Anabaena sp. CA fails to synthesize heterocysts and nitrogenase when grown with KNO3 as the nitrogen source. By contrast, both heterocysts and proheterocysts are synthesized in NH4Cl-containing media to a level nearly commensurate with cells grown in the absence of combined nitrogen. The growth rate of the organism in NH4Cl-containing media was similar to that obtained with KNO3 as the nitrogen source and was independent of the presence of N2 in the atmosphere. Thus, our results indicate that the organism assimilated nitrate and ammonium nitrogen equally well to meet the nitrogen requirements for growth. Moreover, in contrast to previous studies with other cyanobacteria, the repressor singal for heterocyst differentiation in Anabaena sp. CA is not derived from the metabolism of ammonia but appears to be involved with nitrate metabolism. Nitrogenase activity was partially expressed in NH4Cl-grown cultures. Increasing the level of nitrogenase activity to a value representative of a N2-grown culture required both the inhibition of ammonia assimilation and de novo protein synthesis. An increase in the number of mature heterocysts was not required. The fact that high levels of exogenous ammonia only partially repress the synthesis of proteins required for the maximum expression of nitrogenase activity in Anabaena sp. CA has important implications.